TOWARD A SYNTHESIS OF ACCOUNTING DOCTRINE. - Stead, Gordon W. (The Accounting Review, 1948)
Accounting has been said to perform a service function. It consists to serve commerce, industry, and government. These three branches of economic endeavor are constantly evolving into new forms with new content and new orientation. It would thus appear to follow that, in an effort to distill principles of accounting out of the myriad rules of thumb of practice, the subject must be placed in its historical context and those features of it which might change with the form of economic organization differentiated from those which are unlikely to do so. An example in this connection is the change in attitude toward the balance sheet which has taken place over the past one hundred years. Furthermore, the attempts to arrive at principles of accounting have so far been mere compilations of "good things" in the present context, drawn, as it were, out of thin air, without any regard for their functional relationship or historical validity. It is true that these lists have been arranged in what was thought to be an order of merit, but neither the order nor the content has received any marked degree of general acceptance.